ENSURING FOOD SECURITY AMIDST CLIMATE CHANGE: COMPARATIVE ANALYSIS OF THE EUROPEAN UNION AND SOUTHEAST ASIA - Siahaan, Grace Natalia Bornok (Yayasan Baru Haji Samsudin, 2024)
This study compares food security policies in the European Union (EU) and Southeast Asia, focusing on lessons for both regions amid climate change impacts. Using a qualitative approach through literature review, it examines the legal frameworks of the two regions. The EU addresses food security through initiatives like the Common Agricultural Policy (CAP) and the European Green Deal, emphasizing climate change mitigation. In contrast, Southeast Asia, particularly ASEAN, focuses on rural infrastructure, sustainable agriculture, and regional collaboration. The study highlights opportunities for mutual learning, with the EU enhancing inclusivity and Southeast Asia improving policy accountability and enforcement.